Increasing nutrition knowledge and culinary skills in interprofessional healthcare students: an active learning pilot study - Tracy Noerper; Anne Lowery; Geoffrey Wright; Abigail Burka (BMC Medical Education)
Abstract Background Hands-on culinary training can equip healthcare students to educate patients on a healthy diet. Research suggests there is improved self-confidence in patient counseling interactions along with a deeper understanding on the role of an interprofessional healthcare team during hands-on culinary medicine courses. There is a paucity of evidence describing the outcomes that culinary training offers for interprofessional healthcare students in educating individuals who are vulnerable to poverty. The researchers suggested that an active learning, educational program would boost participants’ culinary skills, increase nutrition knowledge, and improve attitudes and confidence in counseling patients with limited means on a healthy diet. Methods The study included a 4-week active learning, educational pilot where nutrition faculty and graduate-level dietetic interns taught nutrition and culinary skills to nursing, physician assistant, and pharmacy students. Each of the four, 2-hour educational sessions focused on cooking skills integrated within nutrition education on topics such as general nutrition, obesity, diabetes, and cardiovascular disease. Recipe selections were based on ingredient cost of $5.00 per person or less, readily accessible ingredients, and basic food preparation skills. Pre-, post-, and 2-month post-intervention survey data were collected and analyzed. Paired sample t-tests were computed to assess for changes between each of the study periods (p  ≤ 0.05). Results Data analysis indicated that participants (N = 14) had a high level of basic culinary skill knowledge at baseline with a mean score of 8.07 (SD = 0.78) out of 10 when compared to nutrition knowledge (M = 7.00, SD = 1.04). Statistically significant improvements (p  ≤ 0.05) were found in pre- to post-assessment participant attitudes toward their counseling abilities in culinary knowledge [95% CI, 1.27 to 4.73; p = 0.002] and culinary techniques/skills [95% CI, 1.25 to 4.75; p = 0.002]. Post- to 2-month post-intervention analysis showed no statistically significant increased mean scores in attitudes, behaviors or counseling characteristics. Conclusions Interprofessional healthcare students may benefit from education that supports improving nutrition knowledge as well as attitudes surrounding their counseling abilities and confidence on a healthy diet, especially with clients who have lower incomes. Future research of hands-on culinary education should aim to balance culinary skills education with improving the nutrition knowledge of interprofessional healthcare students.